Determination of Volumetric Characteristics of FAM Mixtures using X-Ray Micro-Computed Tomography and Their Effects on the Rheological Behavior of the Material. Issue 5 (May 2020) - Osmari, Patrícia Hennig; da Costa, Rogério Ferreira; Aragão, Francisco Thiago Sacramento; Braz, Delson; Barroso, Regina Cély Rodrigues; Nogueira, Liebert Parreiras; Ng, Andressa Ka Yan
Fine aggregate matrix (FAM) has been regarded as a key constituent of asphalt mixtures. Although several design methods have been recently proposed to prepare FAM specimens that represent the materials contained within the asphalt concretes, the volumetric characteristics of FAM may not be uniformly distributed within samples compacted using devices such as the Superpave gyratory compactor (SGC). This can mislead the mechanical analyses conducted with testing specimens that are typically extracted from different locations of the compacted samples, as they can present varying volumetric characteristics. This study employs the advanced micro-computed tomography (CT) scan technique to evaluate the air void distribution within FAM specimens extracted from different locations of SGC samples compacted with distinct air void contents. Rheological tests are performed in a dynamic shear rheometer to determine the dynamic shear modulus of the testing specimens. A statistical analysis is conducted to evaluate potential correlations between the volumetric and the rheological characteristics of the FAMs and to identify locations within the SGC samples from which small cylindrical specimens with similar characteristics can be extracted and used for testing. The adoption of advanced techniques such as the CT scan is essential for the advancement of the knowledge on the complex characteristics of asphalt mixtures, and may facilitate the fabrication of FAMs that are more representative of those that comprise asphalt concretes, as well as allow the use of similar replicates in mechanical tests.